Factors associated with frequent marijuana consumption in young people before admission to juvenile detention centers in Peru - Al-kassab-Córdova, Ali (2023)
Marijuana is the most widely used illicit drug in the world, especially among young people. This study is relevant to policy makers because it expands the knowledge regarding drug use in vulnerable youth, al-lowing health authorities to reduce marijuana consumption via educa-tional, family, and governmental strategies and policies. The objective of this study was to determine the prevalence of frequent marijuana consumption and its associated factors in young people before admission to juvenile detention centers in Peru. The data was taken from the 2016 National Population Census of the Youth Diagnostic and Rehabilitation Centers in Peru. The final sample was made up of 1,848 people with ages between 14 and 22 years old, with a median age of 17 (95.6% males). The variable frequent marijuana consumption was de-fined as the use of marijuana at least once a week, prior to entering the center. The main factors associated with frequent marijuana use were male sex, running away from home before the age of 15, physi-cal abuse during childhood, having a family member who consumed alcohol or drugs frequently, and the presence of criminal gangs in the housing area. Additionally, it was found that living with parents up to a specific critical age decreases the probability of frequent use of marijuana in young people. These results could aid the development of strategies and public policies that help prevent the consumption of marijuana and other drugs from an early age.